2017
DOI: 10.1080/09638288.2017.1331380
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support as a moderator between perceived discrimination and subjective well-being among people with physical disabilities in Israel

Abstract: The findings reveal that perceived social support has a moderating role in the association between perceived discrimination and subjective well-being among people with physical disabilities, such that those with low and moderate levels of perceived social support showed a negative association between perceived discrimination and subjective well-being, while those with high levels of perceived social support showed no association between perceived discrimination and subjective well-being. Findings are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…In two cross-sectional studies of US adults with varied disability diagnoses, those with more friends reported greater life satisfaction and these friendships attenuated the link between functional impairment and poorer quality of life 59. In an Israeli study, perceived disability discrimination and poorer life satisfaction were only linked in those with low and moderate levels of social support, with no association in those with greater levels of support 60. Further research on disability discrimination is necessary to develop awareness campaigns and to appropriately target individual-level interventions.…”
Section: Discussionmentioning
confidence: 95%
“…In two cross-sectional studies of US adults with varied disability diagnoses, those with more friends reported greater life satisfaction and these friendships attenuated the link between functional impairment and poorer quality of life 59. In an Israeli study, perceived disability discrimination and poorer life satisfaction were only linked in those with low and moderate levels of social support, with no association in those with greater levels of support 60. Further research on disability discrimination is necessary to develop awareness campaigns and to appropriately target individual-level interventions.…”
Section: Discussionmentioning
confidence: 95%
“…However, interventions for elderly persons with disabilities that are more strongly affected by environmental factors than by age should focus more on improvements in living and environmental conditions for physical activities. Moreover, approaches to chronic disease management must consider sociological and family factors [ 33 ]. Rehabilitation training should be provided for elderly persons with disabilities, regardless of age, because improvements in the psychological and physiological functions of these people would improve their quality of life and behaviors; thus control the prevalence of NCD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…83,84 The results of them were mixed. When the stressor was perception, such as discrimination, 82,86 or noncatastrophic, such as taking care of elderly patient or marital adjustment, 81 moderate effect was proven to exist. But when the stressor was catastrophic, like cumulative organ damage in women with systemic lupus erythematosus 85 or taking care of relatives with Alzheimer, 84 the result will show no moderate effect or mixed.…”
Section: Effect Of Community Support and N-social Supportmentioning
confidence: 99%